Targeting STAT3 signaling pathway by curcumin and its analogues for breast cancer: A narrative review - Maryam Golmohammadi; Mohammad Yassin Zamanian; Ahmed Muzahem Al‐Ani; Thaer L. Jabbar; Ali Kamil Kareem; Zeinab Hashem Aghaei; Hossein Tahernia; Ahmed Hjazi; Saad Abdul‐ridh Jissir; Elham Hakimizadeh (Animal Models and Experimental Medicine)
Abstract Background Breast cancer (BC) continues to be a significant global health issue, with a rising number of cases requiring ongoing research and innovation in treatment strategies. Curcumin (CUR), a natural compound derived from Curcuma longa, and similar compounds have shown potential in targeting the STAT3 signaling pathway, which plays a crucial role in BC progression. Aims The aim of this study was to investigate the effects of curcumin and its analogues on BC based on cellular and molecular mechanisms. Materials & Methods The literature search conducted for this study involved utilizing the Scopus, ScienceDirect, PubMed, and Google Scholar databases in order to identify pertinent articles. Results This narrative review explores the potential of CUR and similar compounds in inhibiting STAT3 activation, thereby suppressing the proliferation of cancer cells, inducing apoptosis, and inhibiting metastasis. The review demonstrates that CUR directly inhibits the phosphorylation of STAT3, preventing its movement into the nucleus and its ability to bind to DNA, thereby hindering the survival and proliferation of cancer cells. CUR also enhances the effectiveness of other therapeutic agents and modulates the tumor microenvironment by affecting tumor‐associated macrophages (TAMs). CUR analogues, such as hydrazinocurcumin (HC), FLLL11, FLLL12, and GO‐Y030, show improved bioavailability and potency in inhibiting STAT3, resulting in reduced cell proliferation and increased apoptosis. Conclusion CUR and its analogues hold promise as effective adjuvant treatments for BC by targeting the STAT3 signaling pathway. These compounds provide new insights into the mechanisms of action of CUR and its potential to enhance the effectiveness of BC therapies.